Reseña: E. Carney, Eurydice and the Birth of the Macedonian Power, New York, Oxford University Press, 2019, 177 pp [ISBN 978-0-19-028053-6]. - Ignacio Molina (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2019)
Reseña de E. Carney, Eurydice and the Birth of the Macedonian Power, New York, Oxford University Press, 2019, 177 pp [ISBN 978-0-19-028053-6].